1998
DOI: 10.1111/1469-8986.3520186
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex glucose metabolism and startle eyeblink modification abnormalities in unmedicated schizophrenia patients

Abstract: Attentional modulation of the startle reflex was studied in 16 unmedicated schizophrenia patients and 15 control individuals during the 18F-2-deoxyglucose uptake period for positron emission tomography. In a task involving attended, ignored, and novel tones that served as prepulses, control individuals showed greater prepulse inhibition (PPI) at 120 ms and greater prepulse facilitation at 4,500 ms during attended than during ignored prepulses; the amount of PPI and facilitation during novel prepulses was inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
72
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 25 publications
12
72
1
Order By: Relevance
“…In this same study, unmedicated patients with schizophrenia showed less PPI than healthy controls and no correlation between rGMR and PPI. This study (Hazlett et al, 1998), together with the proposed frontal source of origin for the P50 as derived in the present study, seems to confirm the suggestion that the functional integrity of the prefrontal cortex is important for (though not essential for) sensorimotor gating (PPI) as well as for sensory gating (P50 suppression).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this same study, unmedicated patients with schizophrenia showed less PPI than healthy controls and no correlation between rGMR and PPI. This study (Hazlett et al, 1998), together with the proposed frontal source of origin for the P50 as derived in the present study, seems to confirm the suggestion that the functional integrity of the prefrontal cortex is important for (though not essential for) sensorimotor gating (PPI) as well as for sensory gating (P50 suppression).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fact that both measures were intended to assess the gating construct and both are reduced in patients with schizophrenia, the two measures are nonedundant and fundamentally different. In a study on PPI and glucose metabolism by Hazlett et al (1998), the relative glucose metabolic rate (rGMR) in the frontal lobes of healthy volunteers correlated negatively with the amount of PPI, indicating that higher PPI was associated with increased activity in the frontal lobes. In this same study, unmedicated patients with schizophrenia showed less PPI than healthy controls and no correlation between rGMR and PPI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Owen and Downes (1990) found that patients with frontal lobe damage required more moves to solve the problem, and also exhibited prolonged subsequent thinking time in the SOC task. Our finding that high and low PPI subjects differ in their performance of tasks involving the prefrontal cortex supports the putative role of the prefrontal cortex in the modulation of PPI, a claim which is consistent with previous animal and human studies (Hazlett et al, 1998;Hazlett and Buchsbaum, 2001;Zavitsanou et al, 1999;Bubser and Koch, 1994;Kumari et al, 2003).…”
Section: Relationship Between Neuropsychological Performance and Prepsupporting
confidence: 92%
“…With the longer prepulse to pulse ISI, PPF is thought to be generated by a different mechanism than PPI that is automatic sensorimotor gating of unwanted information or response (Graham, 1975). PPF is an orienting or attentional mechanism by which a prepulse stimulus leads to a stronger startle response (Filion et al, 1993;Hazlett et al, 1998;Wynn et al, 2004). One of the consistent nicotinic effects mediated by the nicotinic cholinergic system is the enhancement of orienting and attention (eg Witte et al, 1997;Levin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%